Epigenetic Regulation of Stromal and Immune Cells and Therapeutic Targets in the Tumor Microenvironment - Kang Liu; Yue Li; Minmin Shen; Wei Xu; Shanshan Wu; Xinxin Yang; Bo Zhang; Nengming Lin (Biomolecules)
The tumor microenvironment (TME) plays a pivotal role in neoplastic initiation and progression. Epigenetic machinery, governing the expression of core oncogenes and tumor suppressor genes in transformed cells, significantly contributes to tumor development at both primary and distant sites. Recent studies have illuminated how epigenetic mechanisms integrate external cues and downstream signals, altering the phenotype of stromal cells and immune cells. This remolds the area surrounding tumor cells, ultimately fostering an immunosuppressive microenvironment. Therefore, correcting the TME by targeting the epigenetic modifications holds substantial promise for cancer treatment. This review synthesizes recent research that elucidates the impact of specific epigenetic regulations—ranging from DNA methylation to histone modifications and chromatin remodeling—on stromal and immune cells within the TME. Notably, we highlight their functional roles in either promoting or restricting tumor progression. We also discuss the potential applications of epigenetic agents for cancer treatment, envisaging their ability to normalize the ecosystem. This review aims to assist researchers in understanding the dynamic interplay between epigenetics and the TME, paving the way for better epigenetic therapy.